2020
DOI: 10.1155/2020/3947162
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Micropropagation of Industrially and Medicinally Useful Plant Aloe trichosantha Berger Using Offshoot Cuttings

Abstract: This study was aimed to develop in vitro micropropagation protocol of Aloe trichosantha Berger using offshoots as explants. MS media supplemented with plant growth regulators helped explants develop shoots within about 14 to 17 days. The mean number of days to shooting has decreased from 16.8 ± 0.8 with 0.5/0.5 mg/L BAP/NAA supplement to 15.5 ± 0.5 with 2.0/0.5 mg/L BAP/NAA. While the mean shoot number has increased with increasing the concentration of BAP supplements, the reverse was true with mean shoot leng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(17 citation statements)
references
References 24 publications
0
17
0
Order By: Relevance
“…In vitro propagation media enriched with 0.20/0.20 mg/L, 4.0/0.20 mg/L, 0.50/0.50 mg/L, and 0.20/0.20 mg/L BAP/NAA have been effective for initiating growth in A. percrassa Tod. [ 7 ], A. vera L. [ 11 ], A. trichosantha Berger [ 12 ], and A. adigratana Reynolds [ 13 ], respectively. BAP and NAA are often used for initiating explants of many aloe species.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In vitro propagation media enriched with 0.20/0.20 mg/L, 4.0/0.20 mg/L, 0.50/0.50 mg/L, and 0.20/0.20 mg/L BAP/NAA have been effective for initiating growth in A. percrassa Tod. [ 7 ], A. vera L. [ 11 ], A. trichosantha Berger [ 12 ], and A. adigratana Reynolds [ 13 ], respectively. BAP and NAA are often used for initiating explants of many aloe species.…”
Section: Resultsmentioning
confidence: 99%
“…1 ( a )). Many other studies have reported shooting in A. adigratana Reynolds, A. percrassa Tod., A. trichosantha Berger, and A. vera L. within two weeks in MS media enriched with 1.0 mg/L BAP in combination with auxins (such as IAA and NAA) [ 7 , 12 14 ].…”
Section: Resultsmentioning
confidence: 99%
“…Several past studies on the Aloe vera plant concentrated on propagation using stems and shoot tips, rooted easily with the formation of whole plants (Hailu et al, 2020). It seems likely that certain obstacles faced by callus formation than the complexities challenged its growth histologically, despite providing the required media and supporting it with reasonable growth regulator types and concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…Samples remained in the culture room in the same condition previously mentioned. Cutting out Aloe vera vegetative branches obtained from cultivation of the apical shoot and stems used a sharp scalpel, with their bases planted upright in 25 ml of agar-solidified MS medium supplemented with 1.0 mg L -1 NAA (Hailu et al, 2020).…”
Section: Culture Of Apical Shootmentioning
confidence: 99%
“…However, the optimum concentration and/or combination of PGRs varies from plant to plant and from genotype to genotype (Molsaghi et al, 2014). The individual effects of various PGRs in efficient micropropagation of Aloe were reported in several studies (Lavakumaran and Seran, 2014;Hailu et al, 2020). Interestingly, 6-benzylaminopurine (BAP) alone was proved to be more effective than the combination of BAP and naphthaleneacetic acid (NAA) for in vitro propagation of A. vera (Danial et al, 2019).…”
Section: Introductionmentioning
confidence: 99%